2005
DOI: 10.1038/nature03566
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the regulation of tubulin by vinblastine

Abstract: Vinblastine is one of several tubulin-targeting Vinca alkaloids that have been responsible for many chemotherapeutic successes since their introduction in the clinic as antitumour drugs. In contrast with the two other classes of small tubulin-binding molecules (Taxol and colchicine), the binding site of vinblastine is largely unknown and the molecular mechanism of this drug has remained elusive. Here we report the X-ray structure of vinblastine bound to tubulin in a complex with the RB3 protein stathmin-like d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
608
1
12

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 660 publications
(639 citation statements)
references
References 28 publications
18
608
1
12
Order By: Relevance
“…In the presence of stathmin, we observed a 50-fold increase in the VLB-tubulin binding constant. The fact that VLB increases stathmin binding on tubulin, and vice versa, is in good agreement with the X-ray structure of the RB3-tubulin complex which revealed that both stathmin and VLB binding induce similar conformational consequences, curving consecutive tubulin dimers [13].…”
Section: Thermodynamic Parameters Of Tubulin Complex Formationsupporting
confidence: 86%
See 2 more Smart Citations
“…In the presence of stathmin, we observed a 50-fold increase in the VLB-tubulin binding constant. The fact that VLB increases stathmin binding on tubulin, and vice versa, is in good agreement with the X-ray structure of the RB3-tubulin complex which revealed that both stathmin and VLB binding induce similar conformational consequences, curving consecutive tubulin dimers [13].…”
Section: Thermodynamic Parameters Of Tubulin Complex Formationsupporting
confidence: 86%
“…However, despite a variety of data from cell lines, the molecular basis of this process is not known. Recent crystallographic data suggest that both VLB and stathmin might act together, since they can bind simultaneously on free tubulin and each results in the curving of tubulin dimer filaments [13]. In this study, we present the first direct evidence of the functional synergy between endogenous stathmin and the antimitotic drug VLB.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Vinca alkaloids, such as vinblastine, vincristine, and vinorelbine, occupy a third binding site that is predominantly in the a-tubulin subunit and sits at the interface between adjacent heterodimers in the protofilament (16). Occupation of this site destabilizes microtubules by inducing a tubulin conformation that favors spiral curvature in the protofilaments (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…However, the binding of dolastatin 15 was inhibited not only by cryptophycin 1 and dolastatin 10, but also by halichondrin B and vinca alkaloids. The vinca domain seems to be located in β-tubulin at the inter-dimer interface between α-tubulin and β-tubulin subunits in each protofiber (Gigant et al 2005), suggesting that these toxins do not bind to the vinca domain itself, but the binding site(s) for these toxins consist(s) of a series of overlapping domains on the surface of tubulin (Cruz-Monserrate et al 2003). This is consistent with the finding that hemiasterlin binds to helix H10 on α-tubulin which interacts across the interdimer interface with helix H6 of β-tubulin (Nunes et al 2005).…”
Section: Fig 11mentioning
confidence: 99%